2014
DOI: 10.4254/wjh.v6.i8.601
|View full text |Cite
|
Sign up to set email alerts
|

Assessing liver injury associated with antimycotics: Concise literature review and clues from data mining of the FAERS database

Abstract: AIM: To inform clinicians on the level of hepatotoxic risk among antimycotics in the post-marketing setting, following the marketing suspension of oral ketoconazole for drug-induced liver injury (DILI). METHODS:The publicly available international FAERS database (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) was used to extract DILI cases (including acute liver failure events), where antimycotics with systemic use or potential systemic absorption were reported as suspect or interacting agents. The reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 56 publications
(58 reference statements)
3
64
0
Order By: Relevance
“…Canalicular BS secretion is one of the major driving forces of bile flow and inhibition of BSEP is a well-characterized mechanism of acquired cholestasis (Stieger, 2010), with the number of drugs inhibiting BSEP constantly growing (Dawson et al, 2012). An analysis of the Food and Drug Administration Adverse Event Reporting System database (http://www.fda.gov/ Drugs/GuidanceComplianceRegulatoryInformation/Surveillance/ AdverseDrugEffects/) revealed that antimycotics are involved in approximately 3% of all DILI cases (Raschi et al, 2014). Moreover, antifungal azoles have been associated with elevated levels of serum liver enzymes as well as liver injury occasionally leading to liver failure (Hann et al, 1993;Gearhart, 1994;Adriaenssens et al, 2001;Chang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Canalicular BS secretion is one of the major driving forces of bile flow and inhibition of BSEP is a well-characterized mechanism of acquired cholestasis (Stieger, 2010), with the number of drugs inhibiting BSEP constantly growing (Dawson et al, 2012). An analysis of the Food and Drug Administration Adverse Event Reporting System database (http://www.fda.gov/ Drugs/GuidanceComplianceRegulatoryInformation/Surveillance/ AdverseDrugEffects/) revealed that antimycotics are involved in approximately 3% of all DILI cases (Raschi et al, 2014). Moreover, antifungal azoles have been associated with elevated levels of serum liver enzymes as well as liver injury occasionally leading to liver failure (Hann et al, 1993;Gearhart, 1994;Adriaenssens et al, 2001;Chang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Different drugs have been convincingly documented to cause liver injury in numerous case reports and case series[10]. Paracetamol has been consistently reported as a leading cause of acute liver failure, whereas chlorpromazine, halothane, sulpiride and amoxicillin-clavulanate such as found to be the most common drugs leading to hepatotoxicity in all prospective studies[11].…”
Section: Suspecting and Diagnosing Dili: A Current Dilemmamentioning
confidence: 99%
“…5–7 Few studies have examined the relative and absolute risks of acute liver injury associated with use of oral azole antifungals in clinical practice, and none have evaluated laboratory tests of liver inflammation or function. Moreover, it remains unclear whether chronic liver disease increases the risk of azole-associated acute liver injury.…”
mentioning
confidence: 99%